Estilos de vida en los adolescentes de la casa de acogida Don Bosco - Breña, 2021 - Candela Casas, Maricarmen (2021)
Introduction: To speak of a healthy lifestyle is to consider it as a fundamental element for an optimal development of the physical and psychosocial person. A sedentary lifestyle, malnutrition, obesity and the consumption of psychoactive substances have led to the promotion of a healthy lifestyle becoming one of the challenges of today's society, being a latent problem in adolescents. Objective: It seeks to determine the lifestyles of the adolescents at the Don Bosco Shelter in the Breña district, August 2021. Methodology: It is a research with a quantitative, basic approach, it is a non-experimental method and non- experimental design, cross-sectional and simple descriptive type. The study was carried out in a sample taken from 25 adolescents who were between 13 and 17 years old attending the “Don Bosco” Shelter in the Breña district, and a questionnaire was applied to them to be able to measure lifestyles in the dimensions: food and nutrition, physical activity, stress management, responsibility with health, rest and sleep and the consumption of psychoactive substances. Results: 92% of the adolescents living in the “Don Bosco” Shelter presented healthy lifestyles; In the dimensions they presented healthy styles in food and nutrition (84%), physical activity (76%), stress management (60%), rest and sleep (84%) and consumption of psychoactive substances (100%); in responsibility with their health, 52% presented unhealthy lifestyles.Conclusion: Most of the adolescents living in the “Don Bosco” Shelter in the Breña district presented healthy lifestyles.